2009
DOI: 10.1007/s00701-009-0420-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cognitive function during the 1-year period following endarterectomy and stenting of patients with high-grade carotid artery stenosis

Abstract: Patients with severe carotid artery stenosis exhibited mild decline in cognitive function, which was improved after CEA and CAS. RBANS is a suitable test battery for this type of patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…The improvement in cerebral perfusion after CAS, as documented by imaging technologies (Ko et al, 2005;Martin, A. J. et al, 2005;Tavares et al, 2010;Van Laar et al, 2007), has also been documented through questionnaires for dementia that show clinical improvement in scores after CAS (Moftakhar et al, 2005;Takaiwa et al, 2009;Turk et al, 2008). …”
Section: Wwwintechopencommentioning
confidence: 98%
See 2 more Smart Citations
“…The improvement in cerebral perfusion after CAS, as documented by imaging technologies (Ko et al, 2005;Martin, A. J. et al, 2005;Tavares et al, 2010;Van Laar et al, 2007), has also been documented through questionnaires for dementia that show clinical improvement in scores after CAS (Moftakhar et al, 2005;Takaiwa et al, 2009;Turk et al, 2008). …”
Section: Wwwintechopencommentioning
confidence: 98%
“…According to Takaiwa, patients with carotid artery stenosis who scored below average on the questionnaire prior to carotid angioplasty and endarterectomy showed an improvement in cognitive function after the procedures (Takaiwa et al, 2009). Scores were decreased temporarily at 1 week after carotid endarterectomy (CEA), but not after CAS (Takaiwa et al, 2009).…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation
“…53 Analysis of studies that have compared one carotid revascularization technique with another revealed that there is still a great deal of controversy. 6,31,[63][64][65][66][67] Capoccia et al conducted a non-randomized study in which they respected clinical and anatomic criteria to indicate either CEA (20 patients) or CAS (23 patients) and administered mini mental state examinations over the short and medium term to both groups, concluding that CF worsened in the second group only. The authors detected a positive relationship between this finding and a higher rate of lesions detected within 24 hours using diffusion magnetic resonance (0% versus 21%, respectively).…”
Section: Hemodynamic Changes and Repercussions For Cognitive Functionmentioning
confidence: 99%
“…63 In contrast, Takaiwa et al studied 26 patients (15 operated with CAS and 11 operated by CEA) and concluded that although there was no statistical difference between the two techniques in terms of CF, there were improvements in the domains 'memory' and 'attention' after carotid revascularization and these improvements were sustained over time (12 months). 64 Studies that have investigated this subject vary greatly in terms of the following aspects: the point in time at which tests are administered; use of specific Although CAS involves shorter periods of blood flow privation, it appears to cause greater hemodynamic instability when compared with CEA. The combined impact of these competing factors has not yet been fully investigated.…”
Section: Hemodynamic Changes and Repercussions For Cognitive Functionmentioning
confidence: 99%